2016
DOI: 10.1159/000444770
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological Perspectives of Sex Determination

Abstract: Sex determination or the commitment of the embryo to its sexual fate is a fundamental developmental process with paramount consequences in ecology and evolution. This process, whether triggered by environmental factors or genotypic constitution, can be derailed by environmental contaminants that alter the endocrine system, which is a key component of the regulatory network underlying vertebrate sex determination. Here, we review the molecular basis of sex determination, the endocrine components of its regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 118 publications
(154 reference statements)
0
29
0
Order By: Relevance
“…Hormonal manipulation and exposure to exogenous chemicals can cause sex reversal in amphibians with sex chromosomes [Dournon et al, 1990;Orton and Tyler, 2015], and similar manipulations have been conducted with TSD reptiles [Bull et al, 1988;Belaid et al, 2001;Warner and Shine, 2008;Mizoguchi and Valenzuela, 2016] reversing sex from that expected given the temperature of incubation. However, the relevance of these studies to what happens in the wild remains the subject of some conjecture.…”
Section: Definitive Cases Of Environmental Sex Reversal In Wild Reptimentioning
confidence: 99%
“…Hormonal manipulation and exposure to exogenous chemicals can cause sex reversal in amphibians with sex chromosomes [Dournon et al, 1990;Orton and Tyler, 2015], and similar manipulations have been conducted with TSD reptiles [Bull et al, 1988;Belaid et al, 2001;Warner and Shine, 2008;Mizoguchi and Valenzuela, 2016] reversing sex from that expected given the temperature of incubation. However, the relevance of these studies to what happens in the wild remains the subject of some conjecture.…”
Section: Definitive Cases Of Environmental Sex Reversal In Wild Reptimentioning
confidence: 99%
“…These other factors include maternal environmental effects like egg size [19] and yolk steroid hormones [20], which appear to reflect differential maternal investment [21,22]. It may therefore not be surprising that several endocrinedisrupting chemicals have also been found to interfere with sex determination in species with TSD [23]. For instance, embryos of the turtle Trachemys scripta that are incubated at male-producing temperatures often turn into females when exposed to oestradiol [24], different types of polychlorinated biphenyls (PCBs) [25], the herbicide atrazine [26] or other compounds of which the insecticide chlordane is synergistic with oestradiol when applied in combination [24].…”
Section: Sex Determination In Disturbed and Undisturbed Environmentsmentioning
confidence: 99%
“…A recent example includes Tamschick et al [35], who found species-specific reaction norms in the response of three amphibians to exposure to EE2. Mizoguchi & Valenzuela [23] discuss possible species-specific reaction norms to various micropollutants in reptiles.…”
Section: Rapid Evolutionary Responses To Environmentally Disturbed Sementioning
confidence: 99%
“…Endocrine processes provide the foundation for sex determination and subsequent gonadal formation in all vertebrate species. A growing body of literature advocates that endocrine disruption can overcome the sex-determining program irrespective of GSD or ESD (Mizoguchi and Valenzuela, 2016;Golan and Levavi-Sivan, 2014;Nakamura, 2010). Thyroid hormones (THs) have pleotropic effects in developing vertebrates, including effects on gonadal development.…”
Section: Introductionmentioning
confidence: 99%